HISTORISITAS HADIS MASA NABI, SAHABAT, TABI’IN DAN ATBA’ AL-TABI’IN - Ali Abdur Rohman; Intan Wulansari (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This article discusses the history of the development of hadith during the time of the Nabi, Sahabat, Ta'abi'in, and Atba'al-Ta'abi'in and . The purpose of writing this article is to find out the state of the hadith at that time and also the way of conveying and receiving the hadith at that time, in addition to several other things related to it. This article is written using library research methods and a historical approach to make it easier to identify the state of hadith during the time of the Nabi, Sahabat, Ta'abi'in, and Atba'al-Ta'abi'in. The Prophet's era was the time of al-wahy wa al-takwin (the descent of revelation to Allah's Messenger and direct recitation to the Saha'bat). Sahabat, era al-tasabbut, wa al-iqlal min al-riwayah (hadith passage restriction). Tabi'in, the era of "ashr al-kitabah wa al-tadwin" (the time when hadiths began to be written and recorded). Atba al-Tibi'in era "ashru al-tahdib wa al-tartibi wa al-istidraqi wa al-jami" (collection of hadith into a book under certain conditions, such as those used by Bukhari and Muslims). The result of this historical tracking is that the condition of the hadith can be known, as can the methods used by hadith scholars in tahammul wal'ada and the progress of each period, including the efforts of hadith scholars to minimize the occurrence of hadith forgery